2021
DOI: 10.3389/fpubh.2021.724995
|View full text |Cite
|
Sign up to set email alerts
|

Recursive Path Model for Health Literacy: The Effect of Social Support and Geographical Residence

Abstract: Background: The public health relevance of health literacy is highlighted by the fact that its higher levels can improve health outcomes and reduce health inequities. In order to design effective interventions for improving health literacy, the relationship between health literacy and other factors such as sociodemographic variables, subjective health and social support must be understood.Objective: Our aim was to test a socioecological model of the determinants of health literacy with a special focus on the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…communities [20] , and families; (d) Patients with spouses have a higher ability to recognize rumors. This may be due to the fact that patients with spouses receive more social support [21] , in the sense that spouses and other relatives provide information to patients, and this therefore leads to patients paying more attention to their health because they have more social responsibilities.…”
Section: Analysis Of Factors Influencing the Ability Of Cag Patients ...mentioning
confidence: 99%
“…communities [20] , and families; (d) Patients with spouses have a higher ability to recognize rumors. This may be due to the fact that patients with spouses receive more social support [21] , in the sense that spouses and other relatives provide information to patients, and this therefore leads to patients paying more attention to their health because they have more social responsibilities.…”
Section: Analysis Of Factors Influencing the Ability Of Cag Patients ...mentioning
confidence: 99%
“…A previous study in Hungary reported no significant difference in HL levels by geographical residence; however, the magnitude of the effect of social support on HL was stronger in rural areas [ 12 ]. A study in China found heterogeneity in HL among different areas, between urban and rural areas, and among different social groups [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…"Social capital" means "the social resources that grow in open social networks or social structures that are based on mutual trust (30)." Social networks, participation, trust, reciprocity, and norms are widely recognized as key elements of social capital (31). In terms of the classification of social capital, the literature usually covers two dimensions: structural and cognitive (32).…”
Section: Introductionmentioning
confidence: 99%